2009
DOI: 10.1086/600101
|View full text |Cite
|
Sign up to set email alerts
|

A New Phylogenetic Diversity Measure Generalizing the Shannon Index and Its Application to Phyllostomid Bats

Abstract: Protecting biodiversity involves preserving the maximum number and abundance of species while giving special attention to species with unique genetic or morphological characteristics. In balancing different priorities, conservation policymakers may consider quantitative measures that compare diversity across ecological communities. To serve this purpose, a measure should increase or decrease with changes in community composition in a way that reflects what is valued, including species richness, evenness, and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
167
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(172 citation statements)
references
References 29 publications
1
167
0
1
Order By: Relevance
“…Faith et al (2009) conclude that phylogenetic diversity indices appear to be much better predictors of EQ than traditional taxonomic indices, however the use of more advanced and precise methods to assess the phylogenetic relationships among benthic animals, e.g. taking into account the relative abundance of taxa would further increase the benefits of their application (Allen et al, 2009 indices have the potential to reveal the processes that structure biological communities but when combined with phylogenetic and taxonomic diversity it will help improve our understanding of how biodiversity interacts with ecosystem processes and environmental constraints. In some cases, the analysis of the usefulness of diversity indices to assess the degradation seems questionable because of the extremely discontinuous distribution of environmental quality even if Authors confirmed their high usefulness in the assessment of anthropogenic degradation of watercourses (Göthe et al, 2015;Saito et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Faith et al (2009) conclude that phylogenetic diversity indices appear to be much better predictors of EQ than traditional taxonomic indices, however the use of more advanced and precise methods to assess the phylogenetic relationships among benthic animals, e.g. taking into account the relative abundance of taxa would further increase the benefits of their application (Allen et al, 2009 indices have the potential to reveal the processes that structure biological communities but when combined with phylogenetic and taxonomic diversity it will help improve our understanding of how biodiversity interacts with ecosystem processes and environmental constraints. In some cases, the analysis of the usefulness of diversity indices to assess the degradation seems questionable because of the extremely discontinuous distribution of environmental quality even if Authors confirmed their high usefulness in the assessment of anthropogenic degradation of watercourses (Göthe et al, 2015;Saito et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…taking into account the relative abundance of taxa (e.g. Allen et al, 2009) would further increase the benefits of their application. However, keeping the family level of determination could allow to exploit the existing bio-monitoring databases.…”
Section: Discussionmentioning
confidence: 99%
“…As propriedades da generalização da função H que se apresenta a seguir estão demonstradas em Casquilho et al (1997) e faladas em Ricotta (2002), no âmbito das medidas de diversidade e biodiversidade em Ecologia ou, mais recentemente, na sua proximidade ao conceito de diversidade filogenética (ALLEN et al, 2009); comporta a introdução de valores intrínsecos ou característicos dos habitats, expressos por números reais positivos, formando um conjunto W = {w 1 ,...,w n }, e podem ser estruturados em ponto ou vetor w.…”
Section: Methodsunclassified